THE INFLUENCE OF SOCIAL MEDIA MARKETING ACTIVITY (SMMA) ON CUSTOMERS` HOTEL BOOKING INTENTION IN MALAYSIA: THE MEDIATING EFFECT OF BRAND IMAGE - Ghazali , Muhammad Syazani; Shahril, Aslinda Mohd; Aziz, Azdel Abdul (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Social media significantly impacts tourism and hospitality by changing how travelers search for and engage with travel information, especially for hotel bookings. Despite these changes in consumer behavior, the effect of social media on hotel decision-making still need to be explored. This study examines how social media marketing activities (SMMAs) affect customers’ hotel booking intentions, focusing on factors like electronic word of mouth, entertainment, interaction, and trendiness. The study also looks at the role of brand image in this process. Guided by the Theory of Stimulus-Organism-Response (SOR), the study collects data through a survey questionnaire from 390 social media users in Malaysia and applies quantitative analysis with SPSS and SmartPLS 4. Findings indicate that trendiness in social media marketing has a significant influence on booking intentions, whereas factors such as word of mouth, entertainment, and interaction show no significant effect. Brand image also plays a key mediating role. These insights benefit hoteliers by highlighting effective areas for social media investment, offering guidance for more targeted and innovative marketing. Future research may further explore factors like interactivity, informativeness, and personalization to enhance social media marketing strategies.